치아 마모 환자에서 수직고경 증가를 동반하여 단일구조 지르코니아 보철물로 완전구강회복을 시행한 증례 - 오경철; 정문규; 김지환; 심준성; Oh, Kyung-Chul; Chung, Moon-Kyu; Kim, Jee-Hwan; Shim, June-Sung (Taehan Chikwa Poch'ol Hakhoe chi, 2012)
Excessive occlusal wear results in unacceptable damage to the occluding surfaces, and can cause pulpal injury, occlusal disharmony, impaired function, and aesthetic deformity. Patients with severely worn dentition need to be classified as several categories relative to the vertical dimension of occlusion (VDO) and the interocclusal distance for the prosthetic space. When treating patients classified as those who have excessive wear without loss of occlusal vertical dimension but with limited space, we could consider treating them at an increased vertical dimension of occlusion. Treatments at an increased vertical dimension of occlusion may provide stability, given that the amount of its increase was minimal, and a perfected occlusion was achieved after enough stabilization period. A 50-year-old male visited the department of Prosthodontics in Yonsei University Dental Hospital with the chief complaint of worn teeth on lower anterior area. Reconstruction at an increased vertical dimension of occlusion was planned. After the compatibility of the new vertical dimension of occlusion had been confirmed under interim fixed restorations, definitive fixed restorations composed of full-contour monolithic zirconia prostheses were placed. This case presents that a satisfactory clinical result was achieved by restoring the worn dentition at an increased vertical dimension of occlusion with an improvement in esthetics and function. 과도한 치아 마모는 교합면에 손상을 야기하고, 치수 병변, 교합 부조화, 기능장애, 심미적 문제 등을 야기할 수 있다. 과도한 치아 마모를 갖고 있는 환자들을 치료하고자 할 때 수직교합고경(vertical dimension of occlusion, VDO)의 상실 여부와 수복을 위한 악간 공간의 적절성 여부에 기반하여 분류를 할 필요가 있다. 본 증례의 환자는 다수 치아들의 마모를 지닌 50세의 남성으로, 과도한 치아 마모가 있지만 수직교합고경의 상실은 없으며 수복을 위한 악간 공간이 부족하였다. 이러한 경우 수직교합고경을 증가시켜 치료를 진행하는 것을 고려할 수 있다. 수직교합고경의 증가를 필요한 범위 내에서 최소로 줄이고, 증가된 수직교합고경 상에서 안정화 기간을 거친 뒤 안정된 교합 접촉을 제공할 수 있다면, 수직고경 증가를 동반한 치료법은 안정성을 가질 수 있다. 본 남성 환자를 치료하기 위해 수직고경의 증가를 동반하여 전치부와 구치부에서 단일구조 지르코니아를 이용한 고정성 보철물로 수복을 하였다. 일련의 치료과정을 통하여 기능적인 면과 심미적인 면에서 만족스러운 결과를 얻었기에 보고하는 바이다.